The Advanced Framework for Evaluating Remote Agents (AFERA): A Framework for Digital Forensic Practitioners - Adams, Richard Brian (Curtin University, 2023)
Digital forensics experts need a dependable method for evaluating evidence-gathering tools. Limited research and resources challenge this process and the lack of multi-endpoint data validation hinders reliability in distributed digital forensics. A framework was designed to evaluate distributed agent-based forensic tools while enabling practitioners to self-evaluate and demonstrate evidence reliability as required by the courts. Grounded in Design Science, the framework features guidelines, data, criteria, and checklists. Expert review enhances its quality and practicality.